Perineal ectopic testis in adult: Experience from tertiary hospital, northern Tanzania. (March 2022) - Ngowi, Bartholomeo Nicholaus; Bright, Frank; Mbwambo, Jasper Said; Mmbaga, Blandina Theophil; Lekei, Esther; Kimolo, Mathias; Mteta, Kien Alfred; Mbwambo, Orgeness Jasper
Abstract: Introduction and importance: Perineal ectopic testis is a rare congenital abnormality mostly diagnosed during childhood period. The diagnosis can be easily reached by physical examination. The treatment of choice is either orchidopexy or orchiectomy through scrotal or inguinal approach. Case presentation: We report a case of 30 year old male with painful perineal mass and empty right hemiscrotum. Ultrasound of the mass was done prior to operative procedure and the ectopic testis was the working diagnosis ever since. At exploration there was no abnormality found on the testis; thus, orchidopexy was done with uneventful postoperative period. Clinical discussion: Ectopic testis is rare congenital anomaly with perineal ectopic testis accounting for only 1% of all cases. Most cases of ectopic testis are diagnosed during childhood period. Our case presented at the age of 30 years, the reason could be either late diagnosis by physician or lack of insight of parents/care takers or both. The late presentation might pose a diagnostic challenge but also the testis may be atrophic or undergo malignant changes. In this case the testis was normal and therefore it was successfully relocated surgically through trans-inguinal approach. Conclusion: It is suggested to make perineal ectopic testis one of the differential diagnoses on painful perineal swelling without ipsilateral testis on any man. Highlights: Perineal ectopic testis is a very rare anomaly that represents a true ectopic location of the tests. It is more rare in adults and young boys. Diagnosis depends on level of suspicious index as it is mostly clinical. Any man presenting with painful perineal swelling in the setting of absent testis should be regarded as having perineal ectopic testis until proved other wise. Trans-inguinal orchidopex offers a safe way of managing perineal ectopic testis as the testis is usually of normal size and the spermatic cord is of adequate length even in adults.